Impact of Engineering Faculty Participation in Decision Making and Commitment on Organizational Citizenship Behaviour - Pavan Kumar, S.; Giri, Vijai N. (Journal of Engineering Education Transformations, 2015)
The standard of educational institutions depends mainly on such teachers who are willing to exert significant efforts beyond their formal job requirements. The present study examined the impact of teachers’ participation in decision making and commitment on organizational citizenship behaviour. Data were collected from 655 teachers working in private engineering colleges, affiliated to Jawaharlal Nehru Technological University Hyderabad, India. Results revealed that participation in technical decisions played important role in predicting organizational citizenship behaviour towards team, and organization. Participation in managerial decisions played significant role in predicting organizational citizenship behaviour towards students, and organization. Apart from the participation in decision making, commitment variables were also identified as predictors of the organizational citizenship behaviour. Affective organizational commitment predicted organizational citizenship behaviour towards organization. Job involvement had significant effect on organizational citizenship behaviour towards students. Group commitment predicted both organizational citizenship behaviour towards team, and organization. Further, results indicated that participation in technical decisions predicted significantly all the forms of commitments such as, affective organizational commitment, job involvement, and group commitment. The study portrayed the interrelationships among the commitment forms. The findings help understand the process that explains how participation in decision making is related to organizational citizenship behaviour.